1 THE EFFECT OF GOVERNMENT GOVERNANCE AND TAX RATIO TO ECONOMIC GROWTH (CASE STUDY IN ASEAN COUNTRIES) - Fini Dya Damarani (Jurnal Ekonomi Pembangunan, 2018)
Good government governance and tax ratio can affect economic growth in a country. The performance of the country's economy is good, indicated by the high rate of economic growth. The purpose of this study is to convince and prove whether tax ratio, government effectiveness, regulatory quality, rule of law and corruption control as a set of good governance affect in economic growth, using data from 6 countries in ASEAN.